Systematic review of childhood and adolescence sedentary behavior: analysis of the Report Card Brazil 2018 - Kelly Samara da Silva; Alexsandra da Silva Bandeira; Priscila Cristina dos Santos; Luís Eduardo Argenta Malheiros; Ana Caroline F. C. de Sousa; Valter Cordeiro Barbosa Filho (Revista Brasileira de Cineantropometria e Desempenho Humano)
The aim of this study was to summarize studies examining the prevalence of sedentary behavior among Brazilian children and adolescents. A systematic review conducted on eight databases (PubMed, Scopus, Web of Science, LILACS, SPORTDiscus, BIREME, Scielo, and Google Scholar). The criteria applied were: original research; samples including Brazilian children and adolescents; to be a school- or population-based survey; observational studies using different measures of sedentary behavior; studies showing the prevalence of at least one component of sedentary behavior. Of the 205 studies included, 104 were analyzed. There was a greater concentration of studies in the southern (n=41) and northeastern (n=18) regions. The components more frequently investigated were watching TV (n=36) and screen time (n=32). Only three studies included children under seven years, and the age range more investigated was 10 to 19 years. Most of the studies used a self-reported questionnaire and showed variability in the cut-off point applied (from 2 to 4 hours/day). The prevalence of adolescents who met recommendations ranged from 9.4% to 68.0% for sedentary behavior (<2 hours/day) and from 16.8% to 67.2% for TV viewing (<2 hours/day). The prevalence ranged from 39.1% to 97.7% for computer use and from 47.7% to 98.0% for videogame use. Most of the studies reported that less than half of the adolescents met the recommendations of sedentary behavior and TV viewing. On the other hand, more than half of them devoted less than two hours a day to computer and videogame use.